2020
DOI: 10.1108/ejtd-10-2019-0172
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of situational factors on individual factors and self-development

Abstract: Purpose Organizations are facing pressure to reduce costs of training and enhancing the role of self-development that is self-driven and contextual in nature as a means to supplement employee development. The purpose of this study is to investigate the influence of individual and situational factors on self-development as well as the moderating role of situational factors. Individual factors are referred to personal characteristics, i.e. learning goal orientation and proactive personality, while situational fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 82 publications
2
16
0
Order By: Relevance
“…TAT asserts that situational signals available in the workplace act as moderators and increase individual cues for learning behavior (Tett and Burnett, 2003). The integration of personal and contextual factors of informal learning has scarcely been addressed in existing literature (Noe et al, 2017;Zia et al, 2020). The conceptual model of the study is based on presage, process and product (3-Ps) of workplace learning (Tynjälä, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…TAT asserts that situational signals available in the workplace act as moderators and increase individual cues for learning behavior (Tett and Burnett, 2003). The integration of personal and contextual factors of informal learning has scarcely been addressed in existing literature (Noe et al, 2017;Zia et al, 2020). The conceptual model of the study is based on presage, process and product (3-Ps) of workplace learning (Tynjälä, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Noe et al (2017) concluded that informal learning is a mix of both personal and contextual factors; however, the combined relationship of these two streams is scarcely investigated (Kyndt et al, 2009(Kyndt et al, , 2016Govaerts et al, 2018), particularly very limited evidence is available from SMEs literature. More importantly, employees' involvement in learning and development activities increases when supported by situational/contextual factors (Orvis and Leffler, 2011;Zia et al, 2020). Feedback environment is a contextual factor that acts as a moderator in person-situation interaction (Young, 2013;Young and Steelman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This article integrates the literature on interpersonal conflict and well-being to show that knowledge hiding is a response to environmental stimuli that affect individual variables. Therefore, this paper heeds recent calls from the literature to understand how situational and individual factors explain employees’ attitudes and behaviors at organizations (Zia et al , 2020).…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 99%
“…Personal resources refer to unique individual characteristics, strengths, and abilities to strive and understand the environment to act accordingly toward the situation (Zia et al, 2020). As the environment is unanticipated, individuals must be concerned about their capabilities through strengthening their control to enable them to explore possible future scenarios (Savickas & Porfeli, 2012).…”
Section: The Influence Of Personal Resources On Career Adaptabilitymentioning
confidence: 99%
“…The extant literature on personal factors found in prior research determines the personal factors as a goal orientation (Creed et al, 2009;Yousefi et al, 2011), meaningfulness and emotional intelligence (Harry, 2017), proactive personality, and learning organization orientation (Zia et al, 2020) that have a direct relationship with career adaptability and selfdevelopment. Therefore, changes in society, technology, job demand, and job autonomy affect the indirect effect of personal variables on career adaptability and self-development.…”
Section: Framework Of Studymentioning
confidence: 99%